DESIGN OF LANDSLIDES TREATMENT WITH COUNTERFORT WALL ON CITY LIMITS ROADS TANAH GROGOT-LOLO KUARO, PASER REGENCY, TANA PASER, THE PROVINCE OF KALIMANTAN TIMUR - Adhitya Prakarsa Aji; Markawie Markawie (CERUCUK, 2018)
The landslides occurred on city limits roads Tanah Grogot-Lolo Kuaro, Paser regency, Tana Paser, causing depletion of the smooth flow of transport from the city towards Grogot Lolo-Kuaro or vice versa. Landslides 8 meters height and 50 meters length. The landslides occurred in September 2015 caused by high rainfall and bad drainage system. So it needs to be done the landslides treatment using retaining wall with Counterfort.The methodology of this planning, first to calculate the forces acting on the retaining walls of the soil due to traffic load and soil stockpile with method of Rankine. Continued calculation of the forces acting on the stake piles using the method of Meyerhoff and Skempton. Then do the calculations to determine the group efficiency of stake piles using Brooms method analysis. After the stake piles were declared safe against lateral load and bearing capacity, perform the calculation of reinforced concrete of soil retaining walls. After that the retaining walls and stake piles of the foundation soil is modeled and analyzed using the Geo Studio software to get the safety factor of the design. Lastly, the calculated volume of work and unit price of the retaining walls to get a budget plan costs.After the retaining walls design brings about a result that is, the dimensions of the walls with 8 m height is 4.2 m width foot wall, 0.6 m high to the foot of the wall and the lower part of the wall width, 0.3 m width of to the top of the wall, 0.4 m for a width of Counterfort and 3 m for the distance between Counterfort with lateral load 63.756 tons. Stake pile received 25.867 tons of vertical load and 9.099 tons of lateral load. Safety factor of slopes after landslides treatment modelled with software Geo Studio, resulting in a value of safety factor 2.956 (> 1.25) which can be said to be secure. Based on the calculation of volume and unit price work, retaining wall Counterfort cost is Rp. 3,572,350,220.0-Keyword: Landslide, Retaining Wall, Counterfort, Slopes Stability